Deterrence of Marijuana use among year 10 and year 11 students in NSW, 1992 - Homel, Ross (ADA Dataverse, 2019)
In light of the current drug policy which acts to deter drug use through law enforcement, the study was undertaken to investigate whether the threat of legal punishment has any influence on marijuana use by high school aged students. Using a proven theoretical model, influence was measured both in terms of direct deterrence (e.g. through perceptions of arrest risk and fear of punishment) and indirect deterrence (e.g. physical and material cost of complying or not complying with the law; moral commitment to the law; and informal sanctions imposed by peers, family, or other significant members of the potential user's social network). Emphasis,however, was placed on the former in order to evaluate the effectiveness of law enforcement on drug use and hence its worth as a method of drug control. Respondents were asked questions on their use of alcohol, cigarettes, marijuana, pain relievers, sedatives, narcotics (e.g. heroin) and other recreational drugs (e.g. stimulants, hallucinogens); the number of times they and/or members of their family had been caught for marijuana possession; the consequences of that arrest; ease, and financial cost, of obtaining marijuana; their perceived risk of being caught for marijuana possession and/or use; their personal view of those who use marijuana and the health risks associated with usage; and the effect the opinions of others has on their own use of marijuana. Background variables include age, sex, parents country of birth, language spoken at home, household composition, and whether the respodent is an Aboriginal or Torres Strait Islander.